The effects of temperature and composition on the thermal inactivation of Escherichia coli (ATCC 25923) in Citrus sinensis juice - Pineda, Joyce B. (University of the Philippines Diliman, 2007)
ABSTRACT The study was conducted to develop a mathematical model to predict the decimal reduction times of Escherichia coli (ATCC 25922) as affected by dilution, brix, pectin content and temperature. The data was fitted into a second-order polynomial model and obtained acceptable statistical values (R^2 = 0.87, Adj R^2 = 0.8005, CV = 21.01%, P<0.05) indicating goodness-of-fit and significance f the data. The regression coefficient showed that only the individual effects of temperature, brix, dilution; quadratic effect of pectin (pectin^2) and the interactive effects of brix and temperature; and dilution and temperature are significant on the response, D value. Temperature was found to have the greatest influence on the response. Dilution was shown to promote more rapid killing at higher temperature. On the contrary, soluble solids were generally found to demonstrate a protective effect on the microorganism. The effect of soluble solids gave contradicting inactivation patterns when temperature is considered. Pectin > 2.5% was found to enhance heat resistance due to its ability to increase viscosity impeding heat transfer. Mathematical and graphical validation demonstrated that the RSM predicts D values were all on the fail-safe region and within the acceptable range Af as well as Bf. To assess the usefulness and effectiveness of the model generated, the study suggests that other strains of Escherichia coli be used.